Effect of calcium pre-rinse and fluoride dentifrice on remineralisation of artificially demineralised enamel and on the composition of the dental biofilm formed in situ - Magalhaes, Ana Carolina; de Almeida Furlani, Tatiana; de Moraes Italiani, Flavia; Iano, Flavia Godoy; Delbem, Alberto Carlos Botazzo [UNESP]; Buzalaf, Marilia Afonso Rabelo (Elsevier B.V., 2007)
Objective: This in situ blind crossover study investigated the effect of calcium (Ca) rinse prior to the use fluoride (F) dentifrice on remineralisation of artificially demineralised enamel and on the composition of biofilm. Design: During four phases of 14 days, 10 volunteers wore appliances containing two artificially demineralised bovine enamel blocks. Three times a day, they rinsed with 10 mL, of Ca (150 mM) or placebo rinse (1 min). A slurry (1:3, w/v) of F (1030 ppm) or placebo dentifrice was dripped onto the blocks. During I min, the volunteers brushed their teeth with the respective dentifrice. The appliance was replaced into the mouth and the volunteers rinsed with water. The biofilm formed on the blocks was analysed for F and Ca. Enamel alterations were evaluated by the percentage of surface microhardness change (%SMHC), cross-sectional microhardness (% mineral volume) and alkali-soluble F analysis. Data were analysed by ANOVA (p < 0.05). Results: the use of the Ca pre-rinse before the F dentifrice produced a six- and four-fold increase in biofilm F and Ca concentrations, respectively. For enamel, the remineralisation was significantly improved by the Ca pre-rinse when compared to the other treatments. There was a significantly higher concentration of alkali-soluble F in enamel when the F dentifrice was used, but the Ca pre-rinse did not have any significant additive effect. Conclusions: According to our protocol, the Ca pre-rinse significantly increased biofilm F concentration and, regardless the use of F dentifrice, significantly enhanced the remineralisation of artificially demineralised enamel. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: enamel; dental biofilm; demineralisation; calcium; fluoride dentifrice